2014
DOI: 10.1111/1365-2656.12231
|View full text |Cite
|
Sign up to set email alerts
|

Cheetahs and wild dogs show contrasting patterns of suppression by lions

Abstract: Summary1. Top predators can dramatically suppress populations of smaller predators, with cascading effects throughout communities, and this pressure is often unquestioningly accepted as a constraint on mesopredator populations. 2. In this study, we reassess whether African lions suppress populations of cheetahs and African wild dogs and examine possible mechanisms for coexistence between these species. 3. Using long-term records from Serengeti National Park, we tested 30 years of population data for evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
152
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(162 citation statements)
references
References 79 publications
(168 reference statements)
6
152
4
Order By: Relevance
“…The comparatively low cost of food acquisition and flexible energy budget of cheetahs compared to that of wild dogs (6) are likely to provide a buffer against varying ecological conditions. This study lends support to suggestions that interspecific competition does not necessarily suppress cheetah populations (27)(28)(29)(30). Instead, it shows that cheetahs are well adapted to the presence of competitors, and costs incurred by travelling drive their energy budgets, rather than those encountered securing prey.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The comparatively low cost of food acquisition and flexible energy budget of cheetahs compared to that of wild dogs (6) are likely to provide a buffer against varying ecological conditions. This study lends support to suggestions that interspecific competition does not necessarily suppress cheetah populations (27)(28)(29)(30). Instead, it shows that cheetahs are well adapted to the presence of competitors, and costs incurred by travelling drive their energy budgets, rather than those encountered securing prey.…”
supporting
confidence: 82%
“…Water from the resulting distillates was then analyzed for 18 O and 2 H enrichment by gas-source isotope-ratio mass spectrometry (Optima, Micromass) (see methods in [42] for oxygen and [43] for hydrogen). The multiple-point intercept method was used to derive elimination rates of oxygen (k o ) and hydrogen (k d ) (30). For each animal, CO 2 production was estimated using two different calculations: (i) We used a two-pool model (44) which incorporates the mean dilution space ratio of both isotopes in the calculation of CO 2 production and is appropriate for use in animals greater than about 5kg (30).…”
Section: Laboratory Methods and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies in other parts of Africa have found a much higher cub survival, even with the presence of lions (e.g., Mills & Mills, 2013). Additionally, recent research has shown that lion numbers do not negatively influence cheetah numbers (Swanson et al., 2014), which is likely because cheetahs adjust their spatiotemporal patterns on a fine scale to avoid immediate risks of these larger, more dominant carnivores (Broekhuis et al., 2013; Vanak et al., 2013). We found that cheetahs preferred areas dominated by semiclosed habitat which could explain why cheetahs preferred the wildlife areas despite the very high lion densities (Elliot & Gopalaswamy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that in the Serengeti‐Mara ecosystem, the viability of the cheetah population depends on cub recruitment in other, more densely vegetated, areas. This source–sink dynamic could also explain why, in the Serengeti, overall lion numbers do not have a negative effect on the cheetah population as whole (Swanson et al., 2014), despite the fact that lion abundance is negatively correlated with the survival and recruitment of cheetah cubs (Durant et al., 2004). In the present study, lion nor spotted hyaena abundance had a negative effect on cheetah cub recruitment despite other studies showing that cheetah cubs are often killed by these predators (Laurenson, 1994) and that a larger number of cubs per litter are recruited in areas without lions compared to areas with lions (Bissett & Bernard, 2011).…”
Section: Discussionmentioning
confidence: 99%